Comprehensive Analysis of Hepatitis Delta Virus Assembly Determinants According to Genotypes: Lessons From a Study of 526 Hepatitis Delta Virus Clinical Strains - Gerber, Athenaïs; Le Gal, Frédéric; Dziri, Samira; Alloui, Chakib; Roulot, Dominique; Dény, Paul; Sureau, Camille; Brichler, Ségolène; Gordien, Emmanuel (Frontiers in Microbiology, 2021)
Human hepatitis Delta virus (HDV) infection is associated to the most severe viral hepatic disease, including severe acute liver decompensation and progression to cirrhosis and hepatocellular carcinoma. HDV is a satellite of hepatitis B virus (HBV) that requires the HBV envelope proteins for assembly of HDV virions. HDV and HBV exhibit a large genetic diversity that extends respectively to eight (HDV-1 to -8) and to ten (HBV/A to /J) genotypes. Molecular determinants of HDV virion assembly consist of a C-terminal Proline-rich domain in the large Hepatitis Delta Antigen (HDAg) protein, also known as the Delta packaging domain (DPD) and of a Tryptophan-rich domain, the HDV matrix domain (HMD) in the C-terminal region of the HBV envelope proteins. In this study, we performed a systematic genotyping of HBV and HDV in a cohort 1590 HDV-RNA-positive serum samples collected between 2001 to 2014, from patients originated from diverse parts of the world, thus reflecting a large genetic diversity. Among these samples, 526 HBV (HBV/A, B, C, D, E and G) and HDV (HDV-1, 2, 3, and 5 to -8) genotype couples that could be obtained. We provide results of a comprehensive analysis of the amino-acid sequence conservation within the HMD and structural and functional features of the DPD that may account for the yet optimal interactions between HDV and its helper HBV.